The impact of natural ventilation on the adaptive reuse of a Taiwanese heritage house: an analysis using anemometers and CFD - Dany Perwita Sari; Yun Shang Chiou; William Sugianto (Journal of Asian Architecture and Building Engineering)
Taiwan is currently experiencing high energy use, particularly in buildings. Traditional houses have the advantage of being able to adapt to their surroundings effectively. Several traditional houses are listed as local heritage in Taiwan’s Guanshan village. Considering these are historical buildings, reuse was intended. The temperature change, however, prevented this house from functioning as well as it once could. The application of modern thermal comforts, such as heaters and air conditioners, may alter the originality and character of a structure. This study aims to investigate the natural ventilation of Base 8, a historic Taiwanese residence in Guanshan, to reduce its energy consumption. An in-depth analysis of the case study, a comprehensive understanding of the passive system, site measurements (anemometers), and CFD simulation are used to maximize the potential of cross ventilation. According to the study, an opening perpendicular to the wind’s path would provide better wind passage than one parallel to it. In addition to reducing energy consumption, the study’s findings could help local governments develop guidelines for restoring historic homes in a way that preserves their original materials while preserving their historical heritage.